The cybersecurity governance in changing the security psychology and security posture: insights into e-procurement - Dawood Gani, Anisha Banu; Fernando, Yudi (Inderscience Enterprises Ltd., 2021)
Security is a consistent and growing concern for e-commerce and e-procurement solutions which demand for secure transactions to ensure the confidentiality, integrity and availability of data. E-procurement is vulnerable to cyberattacks resulting in increasing demand for cybersecurity governance. Cybersecurity governance is needed to manage the cyberattacks and ensure the important assets of the company is well protected. The aim of this study is to identify the practices for an effective cybersecurity governance by examining and synthesising existing cybersecurity and cybersecurity governance maturity models and framework from the literature and industry. This study has selected and compared prominent cybersecurity maturity models such as cybersecurity governance maturity model (CSGMM) and cyber preparedness (cyber prep) framework by adapting the taxonomy of software improvement environments method. From the synthesis, 12 practical measures were identified and recommended to manufacturing firms for an effective cybersecurity governance.